2008
DOI: 10.1159/000161562
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytoclastic Vasculitis as an Onset Symptom of Crohn’s Disease

Abstract: We report the case of an octagenerian who presented with leukocytoclastic vasculitis as the first symptom of Crohn’s disease. The patient was admitted with skin rash on the lower extremities and ankles and episodes of bloody diarrhea. Skin and colon biopsies revealed acute leukocytoclastic vasculitis and moderate Crohn’s disease, respectively. The patient was treated with intravenous corticosteroids in conjunction with antibiotics and per os mesalazine. Symptoms resolved rapidly within 5 days, and the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…The hypercoagulable state associated with IBD is thought to be related, in part, to the overlap between the coagulation cascade and the complement cascade . The association of leukocytoclastic vasculitis (an immune complex disease) with Crohn disease in particular is not well established and has only rarely been documented in case reports . Our data support an underrecognized and underreported association here.…”
Section: Discussionsupporting
confidence: 63%
“…The hypercoagulable state associated with IBD is thought to be related, in part, to the overlap between the coagulation cascade and the complement cascade . The association of leukocytoclastic vasculitis (an immune complex disease) with Crohn disease in particular is not well established and has only rarely been documented in case reports . Our data support an underrecognized and underreported association here.…”
Section: Discussionsupporting
confidence: 63%
“…However, the link between the cutaneous lesions and CD in this patient cannot be excluded. Consistent with the observations reported by Tsiamoulos et al [ 3 ] and Zlatanic et al [ 4 ], the skin lesions related to CD likely have a good response to the immunosuppressant therapy. And, in our case, the aggressive immunosuppressive treatment for cutaneous vasculitis and interstitial lung disease may in fact retard the subsequent development of full-blown CD.…”
Section: Discussionsupporting
confidence: 90%
“…Mader et al [ 2 ] searched in the MEDLINE database and only one case presented with cutaneous leukocytoclastic vasculitis as the initial manifestation of CD 3 months before the bowel disease was reported. Similarly, Tsiamoulos et al [ 3 ] reported a case of an octogenarian with cutaneous vasculitis in the skin as the first symptom of CD 2 months before the bowel disease. The typical pathology patterns of these CD-related cutaneous lesions include vasculitis, extravascular neutrophilia, and granulomatous inflammation [ 1 ].…”
Section: Discussionmentioning
confidence: 97%
“…Cutaneous small-vessel vasculitis is the most common type of cutaneous vasculitis and affects mainly the skin postcapillary venules. 146 The cutaneous picture is typically polymorphous 147 and ranges from palpable purpura to urticarial and necrotic ulcerative lesions predominantly involving the legs (Fig. 10), whereas its extracutaneous, particularly renal, manifestations are relatively uncommon.…”
Section: Vasculitismentioning
confidence: 99%